URBANIZATION AND CARDIOVASCULAR DISEASES IN MODERN SOCIETY - M. V. Tabakaev; G. V. Artamonova (Российский кардиологический журнал)
Nowadays cardiovascular diseases are the primary cause of death of the population nearly in all over the world. According to WHO data, this kind of pathology will keep its leading positions in future, that is presupposed by ageing of population and urbanization processes. The main aim of current review is gathering and analysis of the data on the influence of urbanization on the prevalence of cardiovascular pathology and risk factors. It is revealed that urbanization of territories, together with active socio-economical processes is ambivalent in its influence on the health. Also in developed countries the positive aspects of living in large cities (result of complex active actions for the fight with risk factors) prevail negative (negative ecological situation), that engines a decline of the mortality rate from cardiovascular diseases. In developing countries, contrary, urbanization is linked with higher risk of adverse outcomes of cardiovascular diseases. It marked that not so many fatherland studies available, focused on the complex influences of urbanization processes on population health and prevalence of cardiovascular diseases. All this together creates the fundamentals for novel approaches to study of the problem in modern society.